Holocene seas at Pulau Pinang and Pulau Langkawi: new dates Tosido Nakamura, Hong Djin Tjia - Tosido Nakamura; Hong Djin Tjia (Universiti Kebangsaan Malaysia, 2002)
The radiocarbon ages of four groups of fossil subsea bivalve accumulations and four elevated fossil oyster clusters from the vicinity of Pulau Pinang and from Pulau Langkawi were determined at the Dating and Materials Center of Nagoya University, Japan. The subsea samples indicated that the Pinang Channel remained under water during 1500-1900y B.P. [0 B(efore) P(resent) refers to year 1950] and around 450y B.P. In the northern Strait of Melaka, sea level declined regional from + 2.5 m aMSL at 4600y B.P. to + 1.25 m aMSL at 1400y B.P. The eight new data is consistent with the established Late Quaternary - Holocene sea level curve of Peninsular Malaysia. In the Langkawi islands several good shoreline indicators (corals and rock-clinging oysters) between 6500 and 9500y B.P. show early Holocene seas that were 20 to 40 metres above the established sea-level curve. The cause of these anomalous positions is still problematic. Drastic geoidal change or rebound of the land surface following impacts by two recent (6500-5000y B.P.) extraterrestrial objects offer the more plausible explanations.